2019
DOI: 10.1128/msphere.00785-19
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanism of the Atypical AP-1-Like Transcription Factor Yap1 in Cryptococcus neoformans

Abstract: The human meningitis fungal pathogen, Cryptococcus neoformans, contains the atypical yeast AP-1-like protein Yap1. Yap1 lacks an N-terminal cysteine-rich domain (n-CRD), which is present in other fungal Yap1 orthologs, but has a C-terminal cysteine-rich domain (c-CRD). However, the role of c-CRD and its regulatory mechanism remain unknown. Here, we report that Yap1 is transcriptionally regulated in response to oxidative, osmotic, and membrane-destabilizing stresses partly in an Mpk1-dependent manner, supportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…SOD2 is required for high-temperature growth and targets superoxide generated by mitochondrial Complex III [30,61] Interestingly, previous work showed that deletion of SOD1 in C. neoformans results in reduced virulence and increased sensitivity to iNOS-mediated macrophage killing [30,61]. In addition, the yap1Δ mutant exhibits reduced dissemination to the brain and slightly reduced overall virulence [59]. We demonstrate that the yap1Δ mutant fails to produce high ploidy titan cells and has a defect in titanide production, and that loss of YAP1 impairs regulation of SOD1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOD2 is required for high-temperature growth and targets superoxide generated by mitochondrial Complex III [30,61] Interestingly, previous work showed that deletion of SOD1 in C. neoformans results in reduced virulence and increased sensitivity to iNOS-mediated macrophage killing [30,61]. In addition, the yap1Δ mutant exhibits reduced dissemination to the brain and slightly reduced overall virulence [59]. We demonstrate that the yap1Δ mutant fails to produce high ploidy titan cells and has a defect in titanide production, and that loss of YAP1 impairs regulation of SOD1.…”
Section: Discussionmentioning
confidence: 99%
“…The AP-1-like transcription factor Yap1 is a stress response protein induced by oxidative stress in C. neoformans, and loss of YAP1 sensitizes cells to a wide variety of oxidative stress compounds (H 2 O 2 , t-BOOH (H 2 O 2 ), diamide (O 2 -)) [59,60].…”
Section: Endogenous Superoxide Is Required For Titan Cell Formation Ymentioning
confidence: 99%
“…We performed RNA sequencing (RNA-seq)-based transcriptome analysis of wild-type and bzp4 Δ, ada2 Δ, and gat201 Δ mutant strains under both basal and capsule-inducing conditions. We did not include the yap1 Δ mutant in this analysis because Yap1 appeared to mainly act upstream of Gat201, and Yap1-dependent transcriptome profiles were partly reported ( 26 ). We also decided to use LIT medium rather than FBS for the capsule-inducing condition because LIT is a better defined medium than FBS.…”
Section: Resultsmentioning
confidence: 99%
“…However, other virulence factors could contribute to the reduced virulence and/or infectivity of the ada2 Δ, yap1 Δ, and gat201 Δ mutants. Notably, all of these mutants show reduced resistance to oxidative, osmotic, and membrane stress ( 22 , 26 ). Bzp4 is positively involved in the production of two major virulence factors, melanin and capsule, but is dispensable for general stress resistance, virulence in the insect host, and murine infectivity ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation